Playing is the Best Remedy Project: Pedagogical Relations Centered on the Children's Cultural Productions - da Silva Mello, André; Rodrigues Galvão, Emmily; Helmer Trindade, Luísa; Lema Del Rio Martins, Rodrigo; Firmino Magalhães Barbosa, Raquel; Gomes de Assis Pimentel, Giuliano (Guará Journal, 2019)
The   article   aims   at   discussing   pedagogical possibilities   that   acknowledge  and  value  the autonomy  and  authorship  of  children  under cancer treatment regarding games and fun activities offered by a Project in the field of cultural entertainment. To do so, it focuses the  activities  of  the  Playing  is  the  Best Remedy  Project  (Projeto  Brincar  é  o  Melhor Remédio),  developed  through  the  partnership between the Learning Center with Children and their Duties (Núcleo de Aprendizagens com as Infâncias e seus Fazeres - NAIF), from the Physical  Education  and Sports  Center,  and  the  Capixaba  Against  Children’s   Cancer   Association   (Associação   Capixaba   Contra   o   Câncer Infantil - ACACCI). It is about a collaborative research-action, which  uses  filed  diary  an photographic  records  as  sources.  The research subjects are 30 children, two Teachers and the Coordinator member  of  the  Project.  The  analyses undertaken,  in  dialogue  with  Children’s  Sociology and with  Daily  basis  Studies,  indicate  that  the  reactive   entry,   combined   with   pedagogical   processes   centered   on  interaction  and  mediation,  they  favor the  children’s  autonomy  and authorship regarding their relations with the fun activities and games offered by the Project.
Keywords: Games; Fun activities; Children; Cancer